2021
DOI: 10.3390/ph14060497
|View full text |Cite
|
Sign up to set email alerts
|

GO-Y078, a Curcumin Analog, Induces Both Apoptotic Pathways in Human Osteosarcoma Cells via Activation of JNK and p38 Signaling

Abstract: Osteosarcoma is the most common primary bone malignancy in teenagers and continues to confer a generally poor prognosis due to its highly metastatic potential. Poor solubility in water and instability of curcumin limits its bioavailability for use in the adjuvant situation to improve the prognosis and the long-term survival of patients with osteosarcoma. To further obtain information regarding the apoptosis induced by a new curcumin analog, GO-Y078, in human osteosarcoma cells, flow cytometric analysis, annexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…To test this hypothesis, we first examined human apoptosis array (ARY009, R&D systems) in SCC‐9 cells. The human apoptosis array contains 35 proteins that associated with apoptotic process as our previous reports 45 . We identified a serial change in the protein amounts (Figure 4A) We found that cleaved caspase‐3 was increased by approximately 2.3‐fold in HO‐3867‐treated SCC‐9 cells compared to the vehicle control (Figure 4B).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…To test this hypothesis, we first examined human apoptosis array (ARY009, R&D systems) in SCC‐9 cells. The human apoptosis array contains 35 proteins that associated with apoptotic process as our previous reports 45 . We identified a serial change in the protein amounts (Figure 4A) We found that cleaved caspase‐3 was increased by approximately 2.3‐fold in HO‐3867‐treated SCC‐9 cells compared to the vehicle control (Figure 4B).…”
Section: Resultssupporting
confidence: 63%
“…The human apoptosis array contains 35 proteins that associated with apoptotic process as our previous reports. 45 We identified a serial change in the protein amounts (Figure 4A) We found that cleaved caspase-3 was increased by approximately 2.3-fold in HO-3867-treated SCC-9 cells compared to the vehicle control (Figure 4B). Nevertheless, we also found that XIAP, cIAP and Survivin were reduced by 60% upon HO-3867 (Figure 4B).…”
Section: Analysis Of Activating Extrinsic and Intrinsic Apoptotic Pro...mentioning
confidence: 92%
“…We can determine the phases of the cell cycle affected by HO-3867, as well as several other cellular components such as DNA, using flow cytometry analysis on U2OS and HOS cells. Summarily, we plated 8 × 105 U2OS and 6 × 10 5 HOS cells in 6 cm dishes and placed them in experimental concentration range (0, 2, 4, 8, and 16 µM) of HO-3867 for 24 h. After propidium iodide (PI) staining, 2 × 105 U2OS and HOS cells were placed in an Eppendorf tube to analyze the cell cycle using a BD AccuriTM C6 Plus personal flow cytometer [28,29].…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Following the protocol given by the manufacturer (BD Biosciences, San Jose, CA, USA), FITC Annexin V Apoptosis Detection Kit I was administered, followed by the analysis of the cell cycle through flow cytometry. Annexin V-FITC apoptosis staining was used in conjugation with PI staining to determine apoptosis from necrosis [29,30].…”
Section: Annexin V-fitc Apoptosis Staining Assaymentioning
confidence: 99%
“…Levels of cellular DNA and membrane annexin V were monitored to determine the cell cycle and apoptotic response of DSK-treated tongue cancer cells, respectively, by using flow cytometry as described previously [42]. In brief, 3.5 × 10 5 /well HSC-3 and 3 × 10 5 /well SCC-9 cells in 6-well plates in response to various concentrations of DSK for 24 h were stained with PI (Invitrogen, Carlsbad, CA, USA), and the analyses of cell cycle distribution were performed with a BD AccuriTM C6 Plus personal flow cytometer (BD Biosciences, San Jose, CA, USA).…”
Section: Flow Cytometrymentioning
confidence: 99%